Physio-Chemical Changes During Repeated Frying of Cooked Oil: A Review - Nayak, Prakash Kumar; Dash, Uma; Rayaguru, Kalpana; Krishnan, Keasvan Radha (Journal of food biochemistry, 2016)
Today, fried foods are very famous everywhere around the world and it can be observed by the increasing number of fast food restaurants in the last few decades. Deep frying of foods at high temperature enhances the sensorial properties which include the unique fried flavor, golden brown color and crispy texture. Chemical reactions like oxidation, polymerization, hydrolysis, etc., take place in the food system, which ultimately alters the physical and chemical properties of fat. Consequently, so many by‐products such as free fatty acids, alcohols, cyclic compounds, dimers and polymers are produced. Therefore, it is necessary to understand the physical and chemical changes during deep fat frying to monitor the quality of fried foods. In this review, we constituted the previous studies on the changes in fats during frying and methods used to analyze the quality of fried oil, in order to explore the areas which require further research. Practical Applications Deep frying is the most common and one of the oldest methods of food preparation worldwide. To reduce the expenses, the oil tends to be used repeatedly for frying. Repeated use of this oil has become a common practice due to low level of awareness among the public about the bad effect of this practice. Nowadays, the consumption of deep‐fried food has gained popularity which may cause increased risk of obesity. When heated repeatedly, changes in physical appearance of the oil will occur such as increased viscosity and darkening in color, which may alter the fatty acid composition of the oil. In this review, we have investigated the detail mechanism of decay of oil and parameters to be measured to know the quality and safety of oil.